The acute effects of methoxphenidine on behaviour and pharmacokinetics profile in animal model - Štefková-Mazochová, Kristýna; Danda, Hynek; Mazoch, Vladimír; Olejníková-Ladislavová, Lucie; Šíchová, Klára; Paškanová, Natálie; Vágnerová, Magdaléna; Jurásek, Bronislav; Ryšánek, Pavel; Šíma, Martin; Šafanda, Adam; Bui, Quang Hiep; et al. (Progress in neuro-psychopharmacology & biological psychiatry, 2025)
Methoxphenidine (MXP) is classified as a new psychoactive substance that has recently emerged on the illicit drug market. Understanding the pharmacological and behavioural profiles of newly emerging drugs is essential for a better understanding of their psychotropic effects and potential toxicity. Therefore, in this study, we investigated a broad range of effects of acute MXP administration: pharmacokinetics in the brain and serum; behaviour (open field and prepulse inhibition), systemic toxicity (lethal dose; LD 50), and histopathology changes in parenchymal organs of Wistar rats. MXP rapidly crossed the blood-brain barrier, reaching peak median concentrations in both serum and brain 30 min post-administration, followed by an elimination phase with a half-life of 2.15 h. Locomotor activity in the open field test displayed a dose-response effect at low to moderate doses (10–20 mg/kg MXP). At higher doses (40 mg/kg), locomotor activity decreased. All doses of MXP significantly disrupted prepulse inhibition and the effect was present during the onset of its action as well as 60 min after treatment. Additionally, MXP demonstrated moderate acute toxicity, with an estimated LD50 of 500 mg/kg when administered subcutaneously. In summary, MXP exhibited a profile similar to typical dissociative anesthetics, producing stimulant and anxiogenic effects at lower doses, sedative effects at higher doses, and disrupting sensorimotor gating. The accumulation of MXP in brain tissue is likely to contribute to acute intoxication in humans, potentially leading to negative experiences. Our findings highlight the potentially dangerous effects of recreational MXP use and underscore the risks of inducing serious adverse health outcomes. •MXP acts as a stimulant at low doses and a sedative at high doses.•MXP disrupts sensorimotor gating across all tested doses.•MXP exhibits moderate acute toxicity.•MXP rapidly crosses the blood–brain barrier.